2020
DOI: 10.1101/2020.01.07.890731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted and passive environmental DNA approaches outperform established methods for detection of quagga mussels,Dreissena rostriformis bugensisin flowing water

Abstract: The early detection of invasive non-native species (INNS) is important to allow for informed management actions. Established monitoring methods require the collection or observation of specimens, which is unlikely at the beginning of an invasion when densities are likely to be low. Environmental DNA (eDNA) analysis is a highly promising technique for the detection of INNS – particularly during the early stages of an invasion.Here, we compared the use of traditional kick-net sampling with two eDNA approaches (t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
(80 reference statements)
1
5
0
Order By: Relevance
“…The observation that HTS was less sensitive than species-specific qPCR is consistent with other studies (Lacoursière-Roussel et al 2016b;Harper et al 2018;Bylemans et al 2019). Nevertheless, the relatively low performance of HTS in Blackman et al (2020a) may be due to the use of a universal primer that presumably targets most animal groups (metazoans), but was not specifically designed for molluscs and, as a result, may preferentially amplify DNA from other, more abundant species and/or other species whose DNA exhibits better matches to the primer sequence. Thus, in the following paragraphs, we detail the development and use of more-specific HTS metabarcodes (e.g.…”
Section: High-throughput Sequencingsupporting
confidence: 86%
See 3 more Smart Citations
“…The observation that HTS was less sensitive than species-specific qPCR is consistent with other studies (Lacoursière-Roussel et al 2016b;Harper et al 2018;Bylemans et al 2019). Nevertheless, the relatively low performance of HTS in Blackman et al (2020a) may be due to the use of a universal primer that presumably targets most animal groups (metazoans), but was not specifically designed for molluscs and, as a result, may preferentially amplify DNA from other, more abundant species and/or other species whose DNA exhibits better matches to the primer sequence. Thus, in the following paragraphs, we detail the development and use of more-specific HTS metabarcodes (e.g.…”
Section: High-throughput Sequencingsupporting
confidence: 86%
“…Metabarcoding HTS methods have been successfully applied to QM-ZM eDNA surveillance efforts, where several surveillance objectives have been met using a variety of primers (Table 3). For example, COI metabarcoding primers, designed to generically target metazoans (Leray et al 2013) and/or marine invertebrates (Geller et al 2013), have been used to specifically detect ZM (Ardura et al 2017) or QM eDNA (Blackman et al 2020a) and to detect QM-ZM eDNA in community-wide surveys (Mychek-Londer et al 2020). Metabarcoding primers targeting 18S and designed to detect crustaceans, molluscs and tunicates (Zhan et al 2013), have also been used alongside HTS to detect AIS at freshwater ports, revealing the presence of QM (Brown et al 2016).…”
Section: High-throughput Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…An unexplored question is to what extent the results of the above single-species studies (qPCR-based) also apply to metabarcoding experiments. Some work has directly compared the sensitivity of qPCR and metabarcoding using non-specific primers (Blackman et al, 2020;Bylemans et al, 2019;Harper et al, 2018;Simmons et al, 2016;Wood et al, 2019). In all these studies, the qPCR assays were shown to be more sensitive for the detection of the study species.…”
mentioning
confidence: 99%